af015654: Agaria - The 'salt of the earth' ends up as the 'wretched of the earth' - The Press; Public Interest Research Group
"Affiche uitgegeven tussen 1991 en 2011 door de Public Interest Research Group (PIRG) India voor solidariteit met de zoutwinners. Afbeelding: kleurenfoto van blote voeten op een zoutberg. Tekst: Agaria - The 'salt of the earth' ends up as the 'wretched of the earth'. Printed at THE PRESS. Issued in Public Interest by Public Interest Research Group 142, Maitri Apartments, Plot No. 28, I.P., Extn. Delhi - 110092 (India) Phone: 2224233. FULL TEXT AVAILABLE AT AMSAB-ISH"